Shedding of dipeptidyl peptidase 4 is mediated by metalloproteases and up‐regulated by hypoxia in human adipocytes and smooth muscle cells. Issue 21 (12th September 2014) - Röhrborn, Diana; Eckel, Jürgen; Sell, Henrike
Abstract : Dipeptidyl peptidase 4 is an important drug target for diabetes and a novel adipokine. However, it is unknown how soluble DPP4 (sDPP4) is cleaved from the cell membrane and released into the circulation. We show here that MMP1, MMP2 and MMP14 are involved in DPP4 shedding from human vascular smooth muscle cells (SMC) and MMP9 from adipocytes. Hypoxia increased DPP4 shedding from SMC which is associated with increased mRNA expression of MMP1. Our data suggest that constitutive as well as hypoxia‐induced DPP4 shedding occurs due to a complex interplay between different MMPs in cell type‐specific manner. Abstract : Shedding of DPP4 can be significantly reduced by inhibition of MMPs, cysteine and serine proteases. Different MMPs participate in DPP4 shedding in a cell type‐specific manner. Hypoxia increases DPP4 shedding and expression of MMP1 and MMP9.